Analysis of factors affecting destabilization of a viscous liquid flow in channels - Mamedov, Asiman; Hnativ, Roman; Yakhno, Oleg; Murashchenko, Alena (Zielona Góra: Uniwersytet Zielonogórski)
An analysis of the influence of inertia forces and ponderomotive forces on the destabilization of the flow of viscous fluids in the hydrodynamic initial section is given. Cases of flow of viscous, anomalously viscous and electrically conductive liquids are considered; the degree of influence of mass forces on the destabilization of the flow is estimated.
Keywords: hydrodynamic initial section; ponderomotive forces; length of the initial section; Hartmann number; unstabilized fluid flow